Mitigation of Harmonics Due to Electric Vehicle Charging - Neupane, Rasik; Magar, Sunil Thapa; Pandey, Manish; Simkhada, Abhishek; Bhattarai, Bhrigu Raj (Journal of Engineering and Sciences, 2024)
The increasing adoption of electric vehicles (EVs) has led to an increase in demand for charging infrastructure. However, EV charging can introduce harmonic distortion into the electrical distribution network, causing power losses, reduced efficiency, and equipment damage. This project developed an EV charging system with harmonic reduction to ensure a stable and efficient charging process. The research methodology allowed the team to develop an EV charging system with harmonic reduction that was effective in reducing the total harmonic distortion (THD) level from 56.3% to 1%. The system was also found to be stable and efficient during charging. The findings of this project have the potential to make a significant contribution to the development of EV charging infrastructure. The proposed system can help to mitigate the negative impacts of EV charging on the electrical distribution network, while also ensuring a stable and efficient charging process.